2020
DOI: 10.3390/rs12071194
|View full text |Cite
|
Sign up to set email alerts
|

Shallow Landslide Susceptibility Models Based on Artificial Neural Networks Considering the Factor Selection Method and Various Non-Linear Activation Functions

Abstract: Landslide susceptibility mapping is well recognized as an essential element in supporting decision-making activities for preventing and mitigating landslide hazards as it provides information regarding locations where landslides are most likely to occur. The main purpose of this study is to produce a landslide susceptibility map of Mt. Umyeon in Korea using an artificial neural network (ANN) involving the factor selection method and various non-linear activation functions. A total of 151 historical landslide e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 52 publications
(76 reference statements)
1
26
0
1
Order By: Relevance
“…These sites are both located outside of the Alpine region (Jura mountains and the foothills of the Alps) and on average, have gentler slopes (Baulmes 14 • and Hornbach 21 • ). Steeper slopes tend to be more susceptible to shallow landslides, which is in agreement with other studies that have found slope to be one of their top predictors (Budimir et al, 2015;Goetz et al, 2015;Tien Bui et al, 2016;Oh and Lee, 2017;Persichillo et al, 2017;Lombardo and Mai, 2018;Lee et al, 2020;Nhu et al, 2020b, a).…”
Section: Individual Site Modelssupporting
confidence: 92%
See 2 more Smart Citations
“…These sites are both located outside of the Alpine region (Jura mountains and the foothills of the Alps) and on average, have gentler slopes (Baulmes 14 • and Hornbach 21 • ). Steeper slopes tend to be more susceptible to shallow landslides, which is in agreement with other studies that have found slope to be one of their top predictors (Budimir et al, 2015;Goetz et al, 2015;Tien Bui et al, 2016;Oh and Lee, 2017;Persichillo et al, 2017;Lombardo and Mai, 2018;Lee et al, 2020;Nhu et al, 2020b, a).…”
Section: Individual Site Modelssupporting
confidence: 92%
“…The explanatory variables selected for the statistical evaluation of the shallow landslide points are a combination of variables commonly found in landslide or shallow landslide susceptibility studies (Budimir et al, 2015;Chen et al, 2017;Cignetti et al, 2019;Kavzoglu et al, 2014;Lee et al, 2020;Meusburger and Alewell, 2009;Persichillo et al, 2017;Nhu et al, 2020b, a) and climate-related variables that may explain differences between the sites (e.g., strong precipitation events) from the CHELSA data set (Karger et al, 2017(Karger et al, , 2018. Variables related to land-cover and vegetation are not considered as we filter our study sites to contain only grassland areas.…”
Section: Explanatory Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, quantitative evaluation is the most widely used method in evaluating the susceptibility of geological hazards, such as information value model (Achour et al 2017;Liao et al 2019;Mokhtari and Abedian 2019;Sharma and Mahajan 2019;Chen et al 2020), mathematical statistics method (Bourenane et al 2016;Tien Bui et al 2016;Liao et al 2019;Sharma and Mahajan 2019;Chen et al 2020), certainty factor Zheng et al 2020), logistic regression (LR) (Wang et al 2018;Hu et al 2020), artificial neural network (ANN) (Xu et al 2015;Tien Bui et al 2016;Zhou, et al 2018;Sun et al 2019;Lee et al 2020;Wang et al 2020), decision tree (Zhang et al 2017;Hong et al 2018;Wang et al 2018), support vector machines (SVM) (Li et al 2015;Pham et al 2016;Tien Bui et al 2016;Wang et al 2018;Chen et al 2019;Mokhtari and Abedian 2019;Nguyen et al 2020;Yu and Gao 2020), and so on. These methods mainly use mathematical model to establish the quantitative relationship between geological hazards and evaluation factors, which can quantitatively describe the sensitivity of each evaluation factor in different intervals.…”
Section: Introductionmentioning
confidence: 99%
“…The Geographical Information System (GIS) and remote sensing methods have been used to assess landslide hazards. The landslide hazard maps have been produced using a variety of mathematical techniques, ranging from conventional statistic methods such as frequency ratio (Chen et al, 2020), statistical index and weights-of-evidence (Regmi et al, 2014), and logistic regression (Lombardo & Mai, 2018;Sun et al, 2018) to more recent advanced intelligence methods such as artificial neural network (ANN) (Shahri et al, 2019;Alkhasawneh et al, 2013;Alkhasawneh et al, 2014;Lee et al, 2020;Ortiz & MartĂ­nez-Graña, 2018). ANN is applied to many natural science applications such as speech recognition, human face recognition, classification of satellite images, and recognition of texture.…”
mentioning
confidence: 99%